Knowledge and Attitude Level of Students about Solid Waste Recycling; Kashan University of Medical Sciences - Mazaheri Tehrani A.MSc,; Hosseindoost Gh. MSc,; Miranzadeh M.B.* PhD (International Archives of Health Sciences, 2016)
Aims Increasing of the population and development of urban areas, has led to solid waste generation increasing which is one of the problems and difficulties that put human and environmental health in danger. The aim of present study was to determine the knowledge and attitude level of Kashan University of Medical Sciences’ students about solid waste recycling. Instrument & Methods This cross-sectional study was carried out in the fall of 2012 at the Kashan University of Medical Sciences and all the 250 students studying at nursing, medical, and paramedical schools were participated in it. A researcher-made questionnaire consisting of 20 questions was used to determine the knowledge about and attitude toward solid waste recycling. Data was analyzed by ANOVA, Pearson correlation and independent T test. Findings The knowledge of students was the highest about the definition of recycling (84.4%) and lowest about delivery of recycled materials to badgers (23.6%). Most medical (55.1%) and paramedical (75.3%) students had “weak” and most nursing students (47.1%) had “moderate” knowledge about solid waste recycling. 69.2% of paramedical, 27.3% of medical and 25.5% of nursing students stated that “there is no information about recycling in the university courses”. Conclusion Most of the students of Kashan University of Medical Sciences have weak knowledge regarding to solid waste recycling and their knowledge are different among schools.